Horizontal mergers, involuntary unemployment, and welfare - Oliver Budzinski; Jürgen-Peter Kretschmer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
Standard welfare analysis of horizontal mergers usually refers to two effects: the anticompetitive market power effect reduces welfare by enabling firms to charge prices above marginal costs, whereas the procompetitive efficiency effect increases welfare by reducing the costs of production (synergies). However, demand-side effects of synergies are usually neglected. We introduce them into a standard oligopoly model of horizontal merger by assuming an (empirically supported) decrease in labour demand due to merger-specific synergies and derive welfare effects. We find that efficiency benefits from horizontal mergers are substantially decreased, if involuntary unemployment exists. However, in full employment economies, demand-side effects remain negligible. Eventually, policy conclusions for merger control are discussed.
Keywords: L13; L41; J01; L16; 330; horizontal mergers; involuntary unemployment; efficiency defense; oligopoly; competition